An Explanation of Ultradilution and Potentization in Homeopathy - Allan, Norman (Homeopathy, 2021)
This thesis attempts to explain the phenomena of ultradilution and homeopathic potentization with an anecdotal account of a biotinylated dot-blot demonstration of ultradilution brought to the attention of the Pomeranz laboratory, University of Toronto, in 1989. It is argued that the dot-blots are not only data but that they are also an expression of ultradilution itself. Moreover, it is considered that ultradilution and homeopathic potentization can be explained by: (1) Poincaré's recurrence (the disappearance and return of the signal); (2) succussion, resonance and amplification (preservation of the signal); (3) quantum coherence domains (the nature of the signals); and (4) generation of harmonics (the transformation of the signal).
Keywords: Poincaré's recurrence theorem; ultradilution; potentization; serial dilution; succussion; amplification; resonance; harmonic generation; dot-blot analysis